Efeitos da Isradipina (LOMIR). Agente inibidor de canais de cálcio, no processo de reparo em feridas de extração dental: estudo histológico em ratos - Amorim, José Benedito Oliveira [UNESP] (1995)
In order to make a histological evaluation of the dental alveolus wound healing in presence of the Isradipine (Lomir/Sandoz Pharma), the new calcium channels blockers, forthy-eight albino rats were utilized. These animals were divided in two groups. The animals of group I were considered as control; in group II, after the dental extractions the rats received intraperitonial injections of 2,5 mg/Kg of isradipine, administered a single dose. From each group of animals were sacrificed at 3, 7, 14 and 21 post-operative days. The pieces were fixed, descalcified and embedded in paraffin. The blocks thus obtained were cut at 6 micrometers thick and sections were stained with hematoxylin and eosin for morphological study. According to the results obtained i t was verified that the treated animals did not alter of wound healing after dental extractions